Refining human palaeodietary reconstruction using amino acid δ15N values of plants, animals and humans. (January 2015) - Styring, Amy K.; Fraser, Rebecca A.; Arbogast, Rose-Marie; Halstead, Paul; Isaakidou, Valasia; Pearson, Jessica A.; Schäfer, Marguerita; Triantaphyllou, Sevasti; Valamoti, Soultana Maria; Wallace, Michael; Bogaard, Amy; Evershed, Richard P.
Abstract: An established method of estimating the trophic level of an organism is through stable isotope analysis of its tissues and those of its diet. This method has been used in archaeology to reconstruct past human diet from the stable nitrogen isotope (δ 15 N) values of human and herbivore bone collagen. However, this approach, using the 15 N-enrichment of human bone collagen δ 15 N values over associated herbivore bone collagen δ 15 N values to predict the relative importance of animal protein, relies on the assumptions that: (i) the δ 15 N values of plants consumed by humans and herbivores are identical, and (ii) the 15 N-enrichment between diet and consumer is consistent. Bone collagen amino acid δ 15 N values have the potential to tackle these uncertainties, as they constrain the factors influencing bone collagen δ 15 N values. In this study, the δ 15 N values of glutamic acid and phenylalanine in human and herbivore bone collagen isolates from Neolithic sites in Germany, Greece and Turkey were determined by gas chromatography-combustion-isotope ratio mass spectrometry. The fraction of animal protein in total dietary protein consumed by the humans was estimated by: (i) comparing bulk human and herbivore collagen δ 15 N values, (ii) comparing bulk human and herbivore collagen and ancient charred cereal grain δ 15 N values, (iii) comparing human bone collagen δ 15 NGlutamic acid and δ 15 NPhenylalanine values, and (iv) comparing δ 15 NGlutamic acid values of human and herbivore bone collagen and estimated δ 15 NGlutamic acid values of ancient charred cereal grains. Where determined cereal grain δ 15 N values are higher than estimated herbivore forage values, estimates of animal protein consumption are significantly lower, emphasising the importance of the plant nitrogen contribution to human bone collagen. This study also highlights the need for further investigation into: (i) the Δ 15 NConsumer-Diet values of glutamic acid and phenylalanine in terrestrial ecosystems, and (ii) Δ 15 NGlutamic acid-Phenylalanine values of common plant foods in order to improve the accuracy and more widespread applicability of amino acid-based methods for palaeodietary reconstruction. Highlights: Human and faunal bone collagen amino acid (AA) δ 15 N values were determined. We compared 4 diet reconstruction methods using bone collagen and plant δ 15 N values. Different dietary protein estimates are made when grain δ 15 N values are considered. Further investigation is needed into AA δ 15 N values in terrestrial ecosystems.